(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Vocabulary knowledge is a crucial component of second language proficiency. Digital flashcards have become increasingly common in language learning due to technological advancements, but traditional methods such as paper flashcards and vocabulary notebooks remain widely used. This study compares the effectiveness of digital flashcards with traditional techniques by reviewing current research. Findings indicate that digital flashcards—especially those supported by spaced-repetition systems (SRS)—enhance long-term retention, recall accuracy, and learner motivation. Traditional methods, however, support deeper processing through handwriting and enable vocabulary learning in low-technology contexts. The article concludes that a blended approach may provide the greatest benefits.